1982
DOI: 10.1126/science.6283632
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Factor Stimulates Secretion of Melanocyte-Stimulating Hormone from the Rat Pituitary

Abstract: Administration of synthetic ovine corticotropin-releasing factor led to rapid, parallel increases in adrenocorticotropin and alpha-melanocyte-stimulating hormone concentrations in rat plasma. Prior treatment with dexamethasone almost completely blocked the adrenocorticotropin response but not the increase in melanocyte-stimulating hormone. These data demonstrate that corticotropin-releasing factor is a potent stimulator not only of adrenocorticotropin secretion from the corticotrophs of the anterior pituitary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Prior treatment with dexamethasone almost completely blocks the ACTH-response but not the increase in a-MSH [13], imply ing that the ACTH and a-MSH responses to oCRF-41 are mediated by different pathways. In human pituitaries a distinct intermediate lobe cannot be found, but epithelial cells invading the posterior lobe are present in the border region of the anterior and posterior lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Prior treatment with dexamethasone almost completely blocks the ACTH-response but not the increase in a-MSH [13], imply ing that the ACTH and a-MSH responses to oCRF-41 are mediated by different pathways. In human pituitaries a distinct intermediate lobe cannot be found, but epithelial cells invading the posterior lobe are present in the border region of the anterior and posterior lobe.…”
Section: Discussionmentioning
confidence: 99%
“…Corticotropin-releasing hormone (CRH) is a 41 amino acid peptide, which was originally isolated from the ovine hypothalamus (Vale et al, 1981) and has a potent stimulatory action in releasing adrenocorticotronic hormone (ACTH) and (Vale et al, 1981;Proulx-Ferland et al, 1982;Rivier et al, 1982;Turkelson et al, 1982). Immunostaining of paraffin-embedded sections has already revealed that in the human hypothalamus CRH immunoreactivity exists in parvocellular cells of the paraventricular nucleus and nerve fibers in the paraventricular area, in the median eminence, around the pituitary stalk and in the posterior pituitary gland (Pelletier et al, 1983;Mouri et al, 1984 …”
mentioning
confidence: 99%
“…Recent elucidation of the structure of ovine C-RF (3, 4) opens new possibilities for studies of the mechanisms involved in the control of adrenocortical activity. The 41-amino acid peptide is a potent stimulator of corticotropin secretion in vivo in the rat and in adenohypophyseal cells in culture (3,(5)(6)(7).Early studies were suggestive of a role of cyclic AMP as mediator of corticotropin secretion. These studies pertain to the stimulatory effect of theophylline, an inhibitor ofcyclic nucleotide phosphodiesterase, on corticotropin release in intact pituitary glands (8,9).…”
mentioning
confidence: 99%
“…Recent elucidation of the structure of ovine C-RF (3, 4) opens new possibilities for studies of the mechanisms involved in the control of adrenocortical activity. The 41-amino acid peptide is a potent stimulator of corticotropin secretion in vivo in the rat and in adenohypophyseal cells in culture (3,(5)(6)(7).…”
mentioning
confidence: 99%